Pertumbuhan Penjualan, Struktur Aktiva, Ukuran Perusahaan, dan Harga Saham terhadap Struktur Modal dengan Profitabilitas sebagai Variabel Moderasi - Adam Afiezan; Melysa Melysa; Vanesa Julieta Angga; Rosalie Lionar; Jesica Jesica (IPM2KPE, 2022)
This study aims to determine the effect of sales growth, asset structure, company size and stock price on capital structure with profitability as a moderating variable in manufacturing companies listed on the Indonesia Stock Exchange in 2018-2020 both partially and simultaneously. This research method is descriptive quantitative with multiple linear regression analysis. The population in this study has all manufacturing companies listed on the Indonesia Stock Exchange for the 2018-2020 period, namely 177 companies and the sample is 204 units of analysis. The results show that the research reaction is sales growth, asset structure, company size and stock prices partially and together have an influence on capital structure with profitability as a moderating variable in manufacturing companies listed on the Indonesia Stock Exchange for the 2018-2020 period. In conclusion, the profitability variable as a moderating variable partially has a negative influence on the capital structure of manufacturing companies listed on the Indonesia Stock Exchange for the 2018-2020 period. Keywords: Stock Price, Sales Growth, Profitability, Asset Structure, Capital Structure, Company Size